Equation is :( x + 2 )² + ( y - 1 )² = r²( - 4 + 2 )² + ( 1 - 1 )² = r²4 = r², than we will plug in to a formula:( x + 2 )² + ( y - 1 )² = 4x² + 4 x + 4 + y² - 2 y +1 = 4x² + y² + 4 x - 2 y + 1 = 0
the answer is : <span>x2 + y2 + 4x − 2y + 1 = 0 </span>
What do u need help with what the math problem??!?
I am willing to help if I can
Answer: 75
15 multiplied by 5 (how many times it takes 20 to get to 100) gives us 75 :)
Answer:
C is the answer
Step-by-step explanation:
Somehow this was in my test last week , lol